English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i am horrible at algebra(i need the work to be shown here please)

2006-10-14 16:57:15 · 10 answers · asked by George W 1 in Science & Mathematics Mathematics

10 answers

2(6d + 3) = 18 - 3(16 - 3d)
12d + 6 = 18 - 48 + 9d
12d + 6 = -30 + 9d (Subtract 9d and 6 from both sides)
3d = -36 (Divide both sides by 3)
d = -12

Check:
2(6(-12) + 3) = 18 - 3(16 - 3(-12))
2(-72 + 3) = 18 - 3(16 + 36)
2(-69) = 18 - 3(52)
-138 = 18 - 156
-138 = -138
QED

2006-10-15 07:57:28 · answer #1 · answered by CSUFGrad2006 5 · 0 0

First, multiply to get rid of the parenthesis.
2(6d + 3) = 18 - 3(16 - 3d)
12d + 6 = 18 - 48 + 9d (notice that -3 times -3d = +9d)
Now, add like terms
12d + 6 = -30 + 9d
Subtract 9d from each side
12d - 9d + 6 = -30 + 9d - 9d
3d + 6 = -30
subtract 6 from each side to isolate the d's
3d +6 - 6 = -30 -6
3d = -36
Divide each side by 3 to isolate the d
3d/3 = -36/3
d = -12

2006-10-15 00:07:12 · answer #2 · answered by kevvsworld 3 · 0 0

P.E.M.D.A.S

*step 1: let's multiply because of the PARENTHESIS

> 2(6d + 3)=18 - 3(16 - 3d)
> 12d + 6 = 18 - 48 - 9d

*step 2: transpose similar variables (remember to change the sign from positive to negative and vice versa)

> 12d + 9d = 18 - 48 - 6

*step 3: add or subtract the values

> 21d = -36

*step 4: divide this by 21 because it says "21d = -36"

> 21d / 21 = -36 / 21
> d = -12 / 7

2006-10-15 02:22:15 · answer #3 · answered by Princess Answers 3 · 0 0

2(6d + 3) = 18 - 3(16 - 3d)
12d + 6 = 18 - 48 + 9d
12d - 9d = -30 - 6
3d = -36
d = -12

2006-10-15 00:48:39 · answer #4 · answered by TheresaE 2 · 0 0

2(6d + 3) = 18 - 3(16 - 3d)
12d + 6 = 18 - 48 + 9d ... distributive property
3d + 6 = 18 - 48 ... subtract 9d from both sides
3d + 6 = -30 ... 18 - 48 = -30
3d = -36 ... subtract 6 from both sides
d = -12 ... divide both sides by 3

2006-10-15 00:10:05 · answer #5 · answered by whiteboy24 2 · 0 0

2(6d + 3)=18 - 3(16 - 3d)
12d+6=18-48+9d
12d-9d=18-48-6
3d=-36
d=-12

2006-10-15 00:03:23 · answer #6 · answered by yupchagee 7 · 0 0

2(6d+3)=18-3(16-3d)
12d+6=18-48+9d
12d-9d=18-48-6
3d=-30-6
3d=-36
d=-12

2006-10-15 00:07:02 · answer #7 · answered by Lacey 5 · 0 0

Do your own homework...If you always ask people on Yahoo Answers to do it for you, you will not learn. All of your questions today were for your homework...and the reason why you wanted to see the work is because YOUR TEACHER DID TOO. Don't be lazy and do the little bit of work that is expected of you.

2006-10-15 01:20:17 · answer #8 · answered by Niels B 2 · 0 0

You want to start by getting the unknown (d) on the same side of the equals sign....

2006-10-15 00:00:00 · answer #9 · answered by Anonymous · 0 0

d=1 sorry icant show the work idid it in my head

2006-10-15 00:04:27 · answer #10 · answered by v1p3r420 1 · 0 0

fedest.com, questions and answers